Complications Following Arthroscopic Rotator Cuff Tear Repair: A Systematic Review of Terms and Definitions With Focus on Shoulder Stiffness. Issue 6 (16th June 2015) - Audigé, Laurent; Blum, Raphael; Müller, Andreas M.; Flury, Matthias; Durchholz, Holger
Background: Valid comparison of outcomes after surgical procedures requires consensus on which instruments and parameters should be used, including the recording and evaluation of surgical complications. An international standard outlining the terminology and definitions of surgical complications in orthopaedics is lacking. Purpose: This study systematically reviewed the literature for terms and definitions related to the occurrence of negative events or complications after arthroscopic rotator cuff repair (ARCR) with specific focus on shoulder stiffness. Study Design: Systematic review; Level of evidence, 4. Methods: PubMed, EMBASE, Cochrane Library, and Scopus databases were searched for reviews, clinical studies, and case reports of complications associated with ARCR. Reference lists of selected articles were also screened. The terminology of complications and their definitions were extracted from all relevant original articles by a single reviewer and verified by a second reviewer. Definitions of shoulder stiffness or equivalent terms were tabulated. Results: Of 654 references published after 2007 and obtained from the search, 233 full-text papers (44 reviews, 155 studies, 31 case reports, and 3 surgical technique presentations) were reviewed. Twenty-two additional references cited for a definition were checked. One report defined the term surgical complication . There were 242 different terms used to describe local events and 64 to describe nonlocal events. Furthermore, 16 definitions of terms such as frozen shoulder, shoulder stiffness, or stiff painful shoulder were identified. Diagnosis criteria for shoulder stiffness differed widely; 12 various definitions for restriction in range of motion were noted. One definition included a gradation of stiffness severity, whereas another considered the patient's subjective assessment of motion. Conclusion: The literature does not consistently report on complications after ARCR, making valid comparison of the incidence of these events among published reports impossible. Specifically, the variation in criteria used to diagnose shoulder stiffness is problematic for valid and accurate reporting of this event. A standard for reporting this event and other complications after ARCR is needed. Clinical Relevance: This review serves as the basis for the development of a uniform documentation process for shoulder stiffness and the standardization of complication definitions in ARCR following international consensus.